Growth Kinetics of Refractory Metal Silicide under Radiation Induced Interstitial Mechanism: An Analytical Approach - S. O. Akintunde; P. A. Selyshchev; D. O. Kehinde (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Refractory metal silicides are widely used in microelectronics and also important in high-temperature applications. This is due to their excellent thermal stability, high electrical conductivity, and mechanical strength. Conventional silicide formation typically occurs through thermal annealing. In this process, metal and silicon atoms interdiffuse. This interdiffusion occurs at elevated temperatures. However, under irradiation, atomic transport mechanisms are significantly altered. This change leads to enhanced diffusion. As a result, silicide formation can occur at lower temperatures. A theoretical model is developed to describe radiation-induced interstitial diffusion as the dominant mechanism during the formation of thin-film refractory metal silicide. Under irradiation, interstitial atoms are generated in both the metal and silicon layers. This process facilitates atomic transport. The metal interstitial atoms then diffuse toward the silicide/silicon interface through an interstitial mechanism. Similarly, silicon interstitial atoms migrate toward the metal/silicide interface. This also occurs via an interstitial mechanism. The silicide layer forms as a result of chemical reactions between metal and silicon interstitial atoms at these interfaces. The growth of the silicide layer follows a diffusion-limited rate governed by parabolic kinetics. The theoretical analysis indicates a distinct behaviour under irradiation. In such conditions, two interstitial atoms simultaneously contribute to silicide growth. This contrasts with non-irradiation conditions, where diffusion is typically governed by a single dominant atomic species. The effect is particularly pronounced in refractory metal silicides. The interstitial atomic densities were estimated from the model. These estimates correspond to both the irradiated refractory metal and silicon layers. The results indicate that silicide growth kinetics strongly depend on the defect generation rate in both layers. The influence of defect generation rate on silicide growth kinetics is significant. As the defect generation rate increases, the thickness of the silicide layer also increases. This enhancement is primarily due to the elevated interstitial densities resulting from higher defect generation rates in both irradiated layers. This effect is observed even at a low irradiation temperature. This temperature is significantly below the threshold required for silicide formation under non-irradiation conditions.